Methanation of CO2 on bulk Co–Fe catalysts. (3rd November 2021) - Ischenko, Olena V.; Dyachenko, Alla G.; Saldan, Ivan; Lisnyak, Vladyslav V.; Diyuk, Vitaliy E.; Vakaliuk, Anna V.; Yatsymyrskyi, Andrii V.; Gaidai, Snizhana V.; Zakharova, Tetiana M.; Makota, Oksana; Ericsson, Tore; Häggström, Lennart
Abstract: The efficiency of CO2 methanation was estimated through gas chromatography in the presence of Co–Fe catalysts. Scanning electron microscopy, X-ray powder diffraction, X-ray photoelectron spectroscopy, and Mössbauer spectroscopy were applied for ex-situ analysis of the catalysts after their test in the methanation reaction. Thermal programmed desorption mass spectroscopy experiments were performed to identify gaseous species adsorbed at the catalyst surface. Based on the experimental results, surface reaction model of CO2 methanation on Co–Fe catalysts was proposed to specify active ensemble of metallic atoms at the catalyst surface, orientation of adsorbed CO2 molecule on the ensemble and detailed reaction mechanism of CO2 →CH4 conversion. The reaction step when OH group in the FeOOH complex recombined with the H atom adsorbed at the active ensemble to form H2 O molecule was considered as the rate-limiting step. Graphical abstract: Image 1 Highlights: The efficiency of CO2 methanation was estimated in the presence of Co–Fe catalysts. Dissociation of CO2 molecules into discrete C and O atoms was confirmed. Fast production of CH4 and slow H2 O formation was considered in Sabatier reaction. OH group from the FeOOH complex recombine in H2 O molecule using H atom at the surface.